WHAT ARE WE DOING FOR INJURIES; THE BURDEN AND LEVEL OF PREPAREDNESS FOR MASS EMERGENCIES IN KHYBER PAKHTUNKHWA PROVINCE OF PAKISTAN: A QUALITATIVE STUDY - Ahmad, Fayaz; Ul Haq, Zia; Muhammad, Dildar; Qureshi, Muhammad Salman Haider; Ali Shah, Syed Irfan; Kibria, Zeeshan (Journal of Ayub Medical College Abbottabad, 2019)
Background: Injuries are one of the highly prevalent public health problems of Pakistan but still we are unable to develop a mechanism for its quantification and management. To understand the reasons of not doing so we need detailed discussion among the leaders of different stakeholders working in area of injuries. In this study, a focus group discussion (FGD) of provincial health leaders was conducted to explore challenges and gaps and identify opportunities for quantification and management of injuries in the province of Khyber Pakhtunkhwa (KP). Methods: This was a descriptive qualitative study conducted in Khyber Medical University, Peshawar, Pakistan. Study participants were policy makers, academia, senior level health mangers and representatives from international organizations. Purposive sampling was applied to select respondents for FGD from relevant areas to capture diversity of opinions among participants. The data were transcribed verbatim and analyzed thematically through open-coding process. Results: One FGD was conducted in this study with a total of 11 participants. The study participants identified a number of challenges and gaps regarding quantification of injuries’ burden in KP province of Pakistan and preparedness of existing health system to cope with mass emergencies. The discussion yielded four areas of detailed discussion which are; developing a surveillance system for injuries, capacity of District Health Information System, existing level of preparedness at provincial and district level and suggestions for improvement of existing situation with plans for capacity improvement. Conclusions: In countries like Pakistan routine health information system is the better option for quantification of injuries’ burden, but needs review of existing indicators and sheer commitment from field level to higher authorities with due consideration of technology assimilation. A multipronged approach is required for preparedness including; trainings on emergency medicine and skills, incentives for staff to fill vacant posts, well equipped ambulances and provision of other supplies on regular basis. Keywords: Injuries, Focus Group Discussion (FGD), health information system, surveillance system, preparedness.